Frontal Asymmetry in Pilgrims - Szabolcs Kéri (Religions, 2023)
Individuals with religious or spiritual problems experience depressive and anxiety symptoms, together with changes in cognitive style and coping. These problems are associated with altered frontal asymmetry (left greater than right) during the processing of religious stimuli. The present study aimed to investigate the effect of pilgrimage on frontal asymmetry. The participants were 50 individuals experiencing religious or spiritual problems according to DSM-5 criteria. Some 25 of them participated in a two-week religious pilgrimage, and 25 matched volunteers went on non-religious holidays. We recorded resting-state EEG at baseline and after a religious phase (reading a sacred text and listening to music) (NEUVO–CURRY 8X-system, 256-channel). The frontal asymmetry index was calculated for 1 min epochs by subtracting the left electrode sites’ logarithmically transformed alpha frequency from homologous right leads (F4-F3, F8-F7). Anxiety, depressive symptoms, and rumination were assessed using self-report scales. Psychological and EEG assessments were performed before and after the pilgrimage or holiday. The results revealed that individuals experienced less anxiety, depression, and rumination following the pilgrimage. There was a significant reduction in frontal asymmetry during the processing of religious stimuli in pilgrims. We found no similar changes in volunteers who went on a non-religious holiday. These results indicate that frontal asymmetry and negative emotionality are ameliorated during a pilgrimage in individuals with religious or spiritual problems.